Efektivitas Model Pembelajaran Kooperatif Tipe Student Team Achievement Division (STAD) yang Dimodifikasi dengan Tutor Sebaya ditinjau dari Kecerdasan Majemuk Siswa. - Dwi Mei Heni (Jurnal Pendidikan Edutama, 2014)
The Effectiveness Model of Modified Student Team Achievement Division (STAD) Type of Cooperative Learning with Peer tutoring Viewed from the Studentâ€™s Multiple Intelligences. This research was conducted to find out: Which learning model giving better student learning achievement, STAD or modified STAD with peer tutoring. The research population was all XI graders of Vocational School (SMK) throughout Bojonegoro Regency in the school year of 2011/2012. The sampling used was stratified cluster random sampling and then chosen three schools namely SMKN 1 Bojonegoro, SMK Muhammadiyah 2 Sumberrejo, and SMK PGRI 3 Bojonegoro. Technique of analyzing data used was two-way anava 2x3 with different cell. In this research, it can be concluded that The student with the modified STAD type of cooperative learning with peer tutoring have better mathematics learning achievement than the students with STAD type of cooperative learning.Â Keywords : Modified STAD with peer tutoring, Multiple Intelligences, Mathematics Learning Achievement